Reflections on integrated care from those working in and leading integrated respiratory teams*. Issue 2 (4th March 2018) - Roberts, Nicola J.; Ward, Mike; Patel, Irem; Yorke, Janelle; Partridge, Martyn R.
Abstract: The concept of integrated care has been advocated for many years to address some of the challenges faced by the NHS. This report examines the experiences of respiratory healthcare specialists working in an integrated role. Twelve qualitative telephone interviews were undertaken with a range of integrated respiratory specialists and their teams working in both hospitals and the community. A descriptive and thematic approach to data analysis was adopted. Participants were very enthusiastic about their roles and saw themselves as ambassadors for this new way of working. Several key themes were identified from the analysis which participants identified as barriers or enablers to the successful undertaking of an integrated respiratory specialist role. These included the participants' previous work experience and background, the range of multi-disciplinary expertise within or needed for the team, the structure of the team leadership and the measurement of outcomes to evaluate the team. Participants identified the need for clear job descriptions and roles, shared training and standards and appropriate outcome evaluation. More research is needed to understand how these new ways of working are developing and how they can be evaluated.